The effect of climate change on streamflow reduction in Murray-Hotham River catchment, Western Australia - Anwar, Faisal; Bari, M.; Want, Ryan; Islam, Syed (International Water Association, 2011)
This study aimed to model current and future streamflow reduction due to climate change in theMurray-Hotham River catchment of south-west of Western Australia (SWWA). The analysis ofhistorical records in SWWA shows that 19.3% rainfall reduction contributed to 42% streamflow reduction since 1975. The LUCICAT hydrological model was calibrated and validated for the study area. Selected 11 GCMs data, downscaled by Bureau of Meteorology’s Statistical Downscaling Method (BoM-SDM) for A2 and B1 emission scenarios, were considered for future simulation of streamflow. Results revealed that rainfall is projected 12.67% decline by 2055 and 23% decline by 2090 and the streamflow is projected 57.8% decline by 2055 and 84.8% decline by 2090 respectively under A2 scenario. But under B1 scenario, rainfall is projected 10.6% decline by 2055 and remains relatively constant until 2090 but the streamflow shows reduction of 49.1% and 59.1% by 2055 and 2090 respectively. Despite the limitation of the modelling study, the results forecast a dramatic streamflow reduction in Murray-Hotham River catchment by the end of the current century. These findings may be used by water resource managers in conjunction with other strategies to plan for future stability of the water catchments in SWWA.